Live weights, body measurements, reproduction and fleece characteristics of Şavak Akkaraman ewes and rams - Yağcı, S; Baş, S; Tatlıyer Tunaz, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to examine some morphological and physiological characteristics of Şavak Akkaraman sheep and to determine the effects of some environmental factors to this traits. To this end, data related to various characteristics of the Şavak Akkaraman sheep raised under traditional conditions, such as fertility (n = 538), live weight/body measurements (n = 175), and fleece characteristics, were collected from four different farms. The live weights of adult sheep and rams were 50.52 and 76.71 kg, respectively. The body length of sheep and rams was 73.86 and 76.71 cm, wither height 73.63 and 79.41 cm, chest circumference 86.53 and 95.43 cm, rump height 72.19 and 79.35 cm, and rump width 20.12 and 19.77 cm, respectively. The lambing rate was 94%, fecundity and litter size were 97% and 103%, respectively, the number of weaning lambs was 90% and 95%, and survival from birth to weaning time was calculated as 92%. Greasy fleece weight was 2.72 kg, percentage of clean wool 58.20%, Hauter and Barbe fiber length values ​​were 31.98 and 43.01 mm, respectively, thinness was 30.50 µ, fiber elasticity was 30.16% and tensile strength was 26.85 cN/tex. In terms of these specific characteristics, Şavak Akkaraman sheep differ in some differences from other breeds and varieties of Akkaraman sheep. However, further detailed studies are needed to define this variety as a separate breed. Keywords: Sheep; live weight; body measurements; fertility; fleece